Cases in public relations management : the rise of social media and activism - Swann, Patricia (N. York Routledge, 2020)
"Now in its third edition, Cases in Public Relations Management uses recent cases in strategic communication designed to encourage discussion, debate, and exploration of the options available to today's strategic public relations manager, with the help of extensive supplemental materials. Key features of this text include coverage of the latest controversies in current events, discussion of the ethical issues that have made headlines in recent years, and strategies used by public relations practitioners. The problem-based case study approach encourages readers to assess what they know about communication theory, the public relations process, and management practices. New to the third edition: - Eighteen new cases including Snap, Wells Fargo, SeaWorld, United Airlines and Starbucks. - Additional emphasis on social media and social responsibility for communication management today - End-of-chapter activities that reinforce concepts Developed for advanced students in strategic communication and public relations, this book prepares them for their future careers as communication and public relations professionals. The new edition features a fully enhanced companion website that includes resources for both instructors and students. Instructors will find PowerPoint Lecture Slides, Case Supplements, Instructor Guides, and Answer Keys for Quizzes and End-of-Chapter Activities. Students will benefit from Quizzes, a Glossary, and Case Supplements"--
Keywords: Public relations; Social media -- Case studies; Public relations; Activism -- Case studies; Publicity in mass media; Public opinion; Mass media; Public welfare; cOMMUNICATIONS